The Relationship Between Social Media Use and Peer Support with Sedentary Behavior Gorontalo State High School 3 - Ahdar Febriansyah Baruwadi; Herlina Jusuf; Yasir Mokodompis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Sedentary behavior is a sedentary behavior characterized by energy expenditure ?1.5 MET (Metabolic Equivalent of Task) such as when in a sitting or lying position. Some common sedentary behaviors include lying down or sitting for a long time, when playing social media, watching movies or videos, or playing games. Peer influence also plays an important role in shaping students' habits and behaviors. Students who do not get support from peers are more likely to behave passively. The purpose of the study was to analyze the relationship between social media use and peer support and sedentary behavior in SMA 3 Negeri Gorontalo. A type of quantitative research with a correlational approach, the research population of all grade XI students amounted to 438 students with a sample of 209 respondents. Data analysis used the spearman rank test. The results of the study were obtained as many as 166 respondents (79.4%) experienced high sedentary behavior, students with the level of social media use alert as many as 139 respondents (66.5%), for peer support was in the high category as many as 163 respondents (78.0%). In conclusion, there was a relationship between social media use and sedentary behavior (pvalue 0.000<0.05), strong relationship strength, r = 0.661, there was a relationship between peer support and sedentary behavior (p-value = 0.000<0.05), moderate relationship strength r = 0.550. Suggestions for students to be wiser in using social media and remind each other in friend groups to do activities that involve physical movements so that sedentary habits can be reduced.